The value of spectrum and the impact of the breakthrough for mobile data: The case of India, Sweden and Thailand - Bengt G. Mölleryd; Jan Markendahl (International Telecommunications Society (ITS), 2012)
This paper presents an analysis of the marginal value of spectrum with a focus on mobile broadband and illustrated by three country cases: India, Sweden and Thailand. The paper use an engineering valuation approach, which refers to savings that can be achieved by acquiring appropriate amount of spectrum rather than to deploy additional sites, to estimate the marginal value of spectrum. It is complemented with a discounted cash flow valuation (DCF) in order to estimate the net present value of spectrum. Valuation of spectrum is a complex issue given that the value is depending upon the availability of spectrum, national spectrum regulation, competitive situation on the market and expectations about the growth of the mobile business. The paper is addressing three research questions: 1) What is the engineering value of spectrum in two country cases, 2) what is the DCF value of 3G spectrum in Thailand, and 3) what do the paid levels at spectrum auctions imply for the marginal value of spectrum. The methodology applied to calculate the engineering value is based on a comparison of different network deployment options using different amounts of spectrum. As spectrum and sites are substitutes it enables us to calculate how many additional sites that are required in order to compensate for an incremental allocation of spectrum. Moreover, the paper compare estimates of the marginal value of spectrum with prices paid at a number of spectrum auctions presented as the value per MHz per population. The contribution of the paper is the development of an approach and estimates of the marginal value for spectrum which could be of interest for regulators when setting reserve prices on spectrum. It could also be an input to corporate spectrum strategies and a contribution to the development of valuation approaches on spectrum.
Keywords: 330